2012
DOI: 10.1155/2012/785825
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Transcriptome in the HPV-Positive Cervical Cancer Microenvironment

Abstract: The human papillomavirus (HPV) directly infects cervical keratinocytes and interferes with TLR signalling. To shed light on the effect of HPV on upstream receptors, we evaluated TLRs 1–9 gene expression in HPV-negative normal and HPV-positive pre-malignant and malignant ex vivo cervical tissue. Quantitative real-time polymerase chain reaction was performed separately for epithelial and stromal tissue compartments. Differences in gene expression were analyzed by the Jonckheere-Terpstra trend test or the Student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 48 publications
(81 reference statements)
7
51
0
1
Order By: Relevance
“…There was not any TLR9 expression among 6 normal cervical tissues and staining was weak in most of condyloma. Our findings were consistent with other reports (Lee et al, 2007;Hasimu et al, 2011;DeCarlo et al, 2012) which also used formalin-fixed and paraffin-embedded tissue specimens providing from Korean, Chinese and Canadian women. They have shown an increasing expression of TLR9 in neoplastic cervical epithelia in the course of progression of the disease, suggesting that TLR9 upregulation could be beneficial to tumor progression and invasiveness of cervical tissue.…”
Section: Figure 1 Hematoxylin and Eosin (He) Staining And Expressionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was not any TLR9 expression among 6 normal cervical tissues and staining was weak in most of condyloma. Our findings were consistent with other reports (Lee et al, 2007;Hasimu et al, 2011;DeCarlo et al, 2012) which also used formalin-fixed and paraffin-embedded tissue specimens providing from Korean, Chinese and Canadian women. They have shown an increasing expression of TLR9 in neoplastic cervical epithelia in the course of progression of the disease, suggesting that TLR9 upregulation could be beneficial to tumor progression and invasiveness of cervical tissue.…”
Section: Figure 1 Hematoxylin and Eosin (He) Staining And Expressionsupporting
confidence: 93%
“…Their action can lead to resistance of tumor cells to CTL and natural killer attacks and evasion from immune surveillance (Zhou et al, 2013). The existence of opposite data in different ethnic population specimens makes a major problem in understanding the role of TLR9 signaling pathway in CC (Yu et al 2010;DeCarlo et al, 2012). It has been reported a decrease of TLR9 mRNA levels with cervical disease severity (Yu et al, 2010) or a gradual decrease in TLR9 expression along with the grade of CIN suggesting TLR9 expression as an early event in the development of CC in Mexican women (MorenoEutimio et al, 2013).…”
Section: Figure 1 Hematoxylin and Eosin (He) Staining And Expressionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are type 1 transmembrane proteins, which can detect invasive pathogenic microorganisms and primarily exist in immune cells, including dendritic cells and macrophages (5). It was previously revealed that TLRs are closely associated with the progression of tumor (5).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously revealed that TLRs are closely associated with the progression of tumor (5). It has been demonstrated that tumor cells are able to promote its growth by employing TLR signal transduction processes (6).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed that the TLR up-regulation expression had been detected in many other tumor cell lines or tumors, especially in the epithelial derived cancer. 17 In addition to TLRs, other genetic polymorphisms in the cytokines pathways might contribute to cancer development, 19 including cytokine IFN, which is a key cytokine involved in the immunity. 20 IFNG polymorphisms had previously shown significant correlation through an increase in higher stage (FIGO III/IV) cervical cancer.…”
Section: Discussionmentioning
confidence: 99%